Peer review of the pesticide risk assessment for the active substance flutianil in light of confirmatory data on the endocrine disruption assessment. (17th October 2022) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Colagiorgi, Angelo; Colas, Mathilde; De Lentdecker, Chloe; Ferilli, Franco; Ippolito, Alessio; Kardassi, Dimitra; Kienzler, Aude; Linguadoca, Alberto; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State Belgium, for the pesticide active substance flutianil, are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory information with regard to the endocrine disruption potential of the substance. The conclusions were reached on the basis of the evaluation of the representative uses of flutianil as a fungicide on grapevine and ornamental crops. Assessments not finalised, together with the missing information identified as being required by the regulatory framework, are listed.